Host-Plant Variations Affect the Biotic Potential, Survival, and Population Projection of Myzus persicae (Hemiptera: Aphididae) - Muhammad Yasir Ali; Tayyaba Naseem; Muhammad Arshad; Ijaz Ashraf; Muhammad Rizwan; Muhammad Tahir; Misbah Rizwan; Samy Sayed; Muhammad Irfan Ullah; Rashad Rasool Khan; Muhammad Bilal Amir; Mingzhen Pan; et al. (Insects, 2021)
The green peach aphid, Myzus persicae Sulzer (Hemiptera: Aphididae), a polyphagous insect pest is a major threat to a wide range of crops worldwide. Aiming to evaluate the life history traits of M. persicae, feeding on different host plants, we used five vegetables: cabbage, Brassica oleracea (Brassicaceae); chinese cabbage, B. rapa (Brassicaceae); chili pepper, Capsicum annum (Solanaceae); crown daisy, Chrysanthemum coronarium (Asteraceae); and eggplant, Solanum melongena (Solanaceae). TWOSEX-MSchart software was used for the statistical analysis about the age-stage, two-sex life table theory. The highest fecundity (69.65 individuals) rate of M. persicae, intrinsic rate of increase (r = 0.425 d−1), finite rate of increase (λ = 1.531 d−1), net reproductive rate (R0 = 69.65 offspring), and shortest mean generation time (T = 9.964 d) were recorded on the chili pepper plant. Whereas, lower fitness occurred on cabbage. The findings attained from population growth parameters indicate that chili pepper is the most susceptible plant, while cabbage is resistant to aphids. Population projection results also supported this statement, as the final total population size on cabbage was significantly lower than other plants. The reported information would be useful for devising integrated pest management programs, particularly those involving M. persicae. This information also suggests the adaptability of M. persicae causing economic damage to these vegetable cultivars.